Pengelolaan Wisata Religi Berbasis Kearifan Lokal: Peluang dan Tantangan Dari Perspektif Hukum - Ketut Kasta Arya Wijaya; Ni Komang Arini Styawati; I Wayan Rideng (Postgraduated Community Service Journal, 2022)
The development of religious tourism in Ped Village has promising prospects. From a legal perspective, the management of religious tourism has its own opportunities and challenges. Therefore, a study of legal aspects is needed so that they are able to seize opportunities from the development of religious tourism and avoid the negative impacts that arise. This PKM seeks to provide an understanding of legal aspects that need to be considered in the development of religious tourism in Ped Village. The method applied is through legal counseling and assistance in preparing the required regulations. The results of the implementation show that religious tourism in Ped Village has the opportunity to be developed, considering that Balinese people are generally very enthusiastic about carrying out religious activities to come to holy places (temples). Religious tourism is developed based on Balinese culture which breathes Hinduism, is magical/sacred and is combined with natural beauty. The challenge faced is the absence of complete and comprehensive regulations in regulating religious tourism. There is no legal instrument that can provide protection for religious tourism objects, so that there is no pollution and damage or harassment of religious tourism objects. It is important to have regulations drafted in the management of religious tourism in Ped Villages that involve stakeholders